PROTECTED AREAS IN BRAZIL: EVOLUTION, LAND USE AND COVER, AND IMPACT ON EMISSIONS INVENTORY - Cantinho, Roberta Zecchini; Linares, Jimmy Alexander Hernandez; Vieira, José Luiz Vieira da Cruz; Assis, Mauro Lucio Rodrigues de; Bustamante, Mercedes Maria da Cunha (Floresta, 2020)
Faced with population growth and intensification of the use of natural resources, Protected Areas (PA) and Indigenous Lands (IL) play a fundamental role in environmental conservation. The carbon increment of preserved vegetation within these areas is accounted for as CO2 removal in the Land Use, Land-Use Change, and Forestry (LULUCF) sector of the National Emissions Inventory. A topological evaluation of overlaps was made of the databases of PAs (full protection and sustainable use) and ILs, showing that they represent 6% of the protected areas. Of the total of PAs and ILs areas, 43% were established by 1994, 26% by 2002, 26% by 2010, and 4% between 2011 and 2016. This evaluation showed that 30% of the territory is within PAs and ILs. In terms of area, 84% is distributed in the Amazon, 9% in the Cerrado, 4% in the Atlantic Forest, 3% in the Caatinga, 0,2% in the Pantanal, and 0,3% in the Pampa. In assessing the use and cover of 2010 of the PAs and ILs created up to this year, it was possible to notice that 68% of the areas within the PAs have preserved vegetation, whereas in ILs, this percentage increases to 89%. Under the Third Emissions Inventory, the removal of vegetation protected in PAs and ILs decreased by 16% of the national net emissions of the LULUCF sector between 2002 and 2010, showing the importance of preserving forests and grasslands.